Sistem Informasi Manajemen Pada Dinas Pangan Kabupaten Labuhanbatu - Ritonga, Siti Marlina; Ikhwan, Ali; Putri, Raissa Amanda (Jurnal Teknologi Sistem Informasi, 2023)
Labuhanbatu District Food Service is an agency that has the task of assisting the Regent, in carrying out the affairs of the field of food, food distribution and food consumption patterns. As for the data processing business at the Labuhanbatu District Food Service, it has been computerized using Microsoft Excel. But it still has shortcomings in its use, such as data can be lost at any time, and for shared use it is still not appropriate to use because users will find it difficult if they want to update data, because the data is not stored in the database. This information management system of data processing based website is built using the laravel framework. The system design method used is to use the waterfall method. This application can make data processing at the Labuhanbatu District Food Service better and support food progress in Labuhanbatu Regency.